Practicing Servant-Leadership: Succeeding Through Trust, Bravery, And ForgivenessPracticing Servant-Leadership: Succeeding Through Trust, Bravery, and Forgiveness, edited by SpearsLarry and LawrenceMichelle. San Francisco: Jossey-Bass, 2004. - Hamilton, Frank (Academy of Management Review, 2005)
The article reviews the book ?Practicing Servant-Leadership: Succeeding Through Trust, Bravery, and Forgiveness,? edited by Larry Spears and Michelle Lawrence.